Developing Instructional Media Artificial Intelligence Of Arabic Language Teaching and Learning - Setiyawan, Adhi Iwan; Rifai, Ikhsan Mohmad (Ijaz Arabi Journal of Arabic Learning, 2025)
Innovation in instructional artificial intelligence (AI) has attracted the interest of learning practitioners and many educational institutions. AI is rooted in offering convenience and solving learning problems. Improving easy and enjoyable Arabic language learning requires the creation and design of instructional technology itself. Challenges and concerns include issues related to academic integrity, stemming from algorithmic bias, incomplete data, inaccurate content, and the potential for reduced human interaction. Research and development were used to develop an Instructional Media AI model. This study used a combination of the three-stage Plomp and ASSURE models. The findings of this study highlight the development of AI for Arabic language students and the advancement of AI design research by examining practical, functional, and effective options. This research includes an analysis of annual scientific production, the most relevant sources, a thematic map, and a factorial analysis. Research Limitations: This study demonstrates the potential of AI not only as a trending topic but also as a valuable resource for instructional development. AI-based instructional development has a speed and interactive variety contributing to deep learning and immersive teaching. The results of this study provide a product in the form of AI-based Arabic language media innovation learning. Concrete evidence of innovative instructional design models developed through chatbot development, steps, and AI-assisted learning media creation products. These findings also serve as a reference for future researchers to more easily identify innovative Technology of Arabic Language Teaching and Learning pedagogical foundations in future research.